Hierarchically ordered macro–mesoporous anatase TiO2 prepared by pearl oyster shell and triblock copolymer dual templates for high photocatalytic activity. Issue 67 (14th November 2018) - Zhao, Jianquan; Liao, Chanjuan; Chen, Xia; Song, Wulin
Abstract : Hierarchically ordered macro–mesoporous anatase TiO2 with photocatalytic activity was prepared using triblock copolymer P123 and natural pearl oyster shell as dual templates. Abstract : Hierarchically ordered macro–mesoporous anatase TiO2 is prepared by combining the supramolecular-templating self-assembly of amphiphilic triblock copolymer P123 with a natural pearl oyster shell in a hard-templating process by a facile sol–gel reaction. The obtained materials are characterized by Raman spectroscopy, X-ray diffraction, N2 adsorption–desorption analysis, scanning electron microscopy, and transmission electron microscopy. The results demonstrate that all TiO2 materials obtained after calcination at various temperatures are in the anatase phase, and interestingly the resultant ordered structure of both macropores and mesopores are well-preserved after calcination at 350 °C or 450 °C, with the walls of macropores composed of ordered mesopores. However, upon calcination at 550 °C or 650 °C, while the ordered macroporous structures remain well-preserved, the mesoporous structures collapse. The photocatalytic activities of the resulting TiO2 materials are also evaluated by photodegradation of rhodamine B under UV light irradiation. The prepared TiO2 calcined at 450 °C shows the highest photocatalytic activity.